Structural, electronic and mechanical properties of sp3-hybridized BN phases. Issue 15 (30th March 2017) - Zhou, Rulong; Dai, Jun; Cheng Zeng, Xiao
Abstract : We present several new sp 3 -hybridized phases of BN and comprehensively study their structural, electronic, and mechanical properties. Abstract : Motivated by the discovery of new phases of carbon under cold high-pressure compression, we performed a global structure search of high-pressure phases of boron nitride (BN). Ten new bulk phases were identified, each energetically more stable than the graphite-like hexagonal BN (h-BN) under high pressures. All ten high-pressure phases could be viewed as involving a stacking of buckled h-BN layers. Some of these solid structures can be fabricated through the cold high-pressure compression of h-BN films. According to the buckling of the h-BN layers, the new BN phases could be classified into three groups. The atomic structures, relative stabilities, electronic structures, and mechanical properties were studied in detail. A strong dependence of the relative stability, band structure, and mechanical properties on the buckling of h-BN was observed. The computed electronic band structures suggested that most of the high-pressure BN phases were insulators with wide and indirect band gaps. The calculated elastic constants and hardness suggested that several of the BN structures were superhard materials with potential applications in materials science and engineering. The computed transition paths indicated that the direct transition from h-BN to four of the new sp 3 -hybridized BN structures, or specifically to w-BN or bct-BN, were likely to occur through cold compression. For the other five of the new BN structures, although deeper local minima existed in the transition path, their formation through cold compression of h-BN was still plausible due to the low transition barrier from the deeper local minima to the targeted structure.